Starting Out: A time-lagged study of new graduate nurses' transition to practice. (May 2016) - Laschinger, Heather K. Spence; Cummings, Greta; Leiter, Michael; Wong, Carol; MacPhee, Maura; Ritchie, Judith; Wolff, Angela; Regan, Sandra; Rhéaume-Brüning, Ann; Jeffs, Lianne; Young-Ritchie, Carol; Grinspun, Doris; et al.
Abstract: Background: As the nursing profession ages, new graduate nurses are an invaluable health human resource. Objectives: The purpose of this study was to investigate factors influencing new graduate nurses' successful transition to their full professional role in Canadian hospital settings and to determine predictors of job and career satisfaction and turnover intentions over a one-year time period in their early employment. Design: A national two-wave survey of new graduate nurses across Canada. Participants: A random sample of 3906 Registered Nurses with less than 3 years of experience currently working in direct patient care was obtained from the provincial registry databases across Canada. At Time 1, 1020 of 3743 eligible nurses returned completed questionnaires (usable response rate = 27.3%). One year later, Time 1 respondents were mailed a follow-up survey; 406 returned a completed questionnaire (response rate = 39.8%). Methods: Surveys containing standardized questionnaires were mailed to participants' home address. Descriptive statistics, correlations, and hierarchical linear regression analyses were conducted using SPSS software. Results: Overall, new graduate nurses were positive about their experiences and committed to nursing. However, over half of new nurses in the first year of practice reported high levels of emotional exhaustion and many witnessed or experienced incivility (24–42%) at work. Findings from hierarchical linear regression analyses revealed that situational and personal factors explained significant amounts of variance in new graduate nurses' job and career satisfaction and turnover intentions. Cynicism was a significant predictor of all four outcomes one year later, while Psycap predicted job and career satisfaction and career turnover intentions. Conclusions: Results provide a look into the worklife experiences of Canadian new graduate nurses over a one-year time period and identify factors that influence their job-related outcomes. These findings show that working conditions for new graduate nurses are generally positive and stable over time, although workplace mistreatment is an issue to be addressed.